Selling the past in films: shaw brothers and the Japanese occupation of Malaya - Yow, Chong Lee; Candida Jau, Emang (UKM Press, 2016)
This article aims to examine the representation of Japanese occupation of Malaya in films produced by Shaw Brothers during the Golden Era of Malay cinema, namely “Sergeant Hassan” (1958) and “Matahari” (1958). Currently, films depicting the past are relatively less prevalent in Malaysia, and scholarly analysis is comparatively less conducted on such films. Hence, the authors try to analyse how the films, in a given context, which reconstruct and reflect the historical past are experienced by the society at large. Bearing in mind that the films are based on a similar subject (Japanese occupation as its backdrop), it is important to determine why different receptions were registered from the audiences on both films. This prompted the authors to examine the reasons why these two films received a different level of popularity from their contemporary audiences (in the late 1950s). In this article, both the textual and contextual analysis will be employed: the former method is used to interpret the meanings constructed through the film’s text and promotional materials for both films. The latter would explore the historical circumstances that shaped both the production and reception of the films. This is mainly through promotional materials as well as secondary sources through interviews conducted by third party researchers who had interviewed Shaw Brothers and those who had experience working with them. The findings of this article indicate that the Shaw Brothers were ambitious with their films projects about the Japanese Occupation by widening the promotion of “Sergeant Hassan” to a wider audience and not limited it solely to the Malays1 . By capitalising on the historical pasts that the contemporary audiences (in the late 1950s) had personally experienced, Shaw Brothers had embarked on the complex relationship of socio-political and economic conditions which had also shaped different receptions towards these films.